Can we still predict the future from the past? Implementing non‐stationary flood frequency analysis in the UK. Issue 1 (3rd December 2019) - Faulkner, Duncan; Warren, Sarah; Spencer, Peter; Sharkey, Paul
Abstract: The Environment Agency in England is investing £2.5 billion with the aim of reducing flood risk to at least 300, 000 homes by 2020/21. Several of the schemes being considered are on rivers that have experienced an upsurge of flooding over recent years. Decisions on whether to invest and how high to build are usually made on the basis of stationary methods of flood frequency analysis that assume the probability of flood flows is unchanging over time. Following successive severe floods in Cumbria, trend tests and non‐stationary flood frequency analysis techniques have been applied. These allow parameters of the frequency distribution to change over time or with some other covariate. The resulting estimates of flow, for the present day, were up to 55% higher than the stationary estimates at river gauges in north‐west England. The results have been incorporated into the scheme appraisal process. A national analysis indicates that there is evidence of upward trends in peak flows at nearly a quarter of river flow gauges across Great Britain. Many rivers show an abrupt increase in flood flows in the late 1990s. Trends tend to occur in upland areas but they are also seen on some rivers across south‐east England.